Scaling agri-technologies for promoting sustainable agriculture and reversing forest degradation In Zambia - Kariuki, Fidelis Wangari; Wafullah, Teresah Nekesah (Bioversity International and the International Center for Tropical Agriculture (CIAT), 2025)
On 13 May 2025, the consultation workshop “Scaling agri-technologies for promoting sustainable agriculture and reversing forest degradation in Zambia” was organized by the CGIAR Centre Alliance of Bioversity International and CIAT through the CGIAR Accelerate for Impact Platform (A4IP). The workshop held in Lusaka, Zambia, brought together a diverse group of stakeholders, including academicians, entrepreneurs, entrepreneurship support organizations (ESOs), farmers associations, governments, policy representatives and researchers to address key challenges related to agricultural technology adoption and climate resilience. This collaborative effort aimed to inform the design of a new initiative promoting agri-technology use to promote both restoring the biodiversity of degraded ecosystems and reducing deforestation along the Lobito line in Zambia. It also aimed to promote sustainable development through using agri-technologies for climate-resilient agricultural practices and livelihoods in Zambia’s Northwestern and Copperbelt provinces.